2020
DOI: 10.1093/cid/ciaa613
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Drug-resistance Profiles Between Persons With Drug-resistant Tuberculosis and Their Household Contacts: A Systematic Review and Meta-analysis

Abstract: Background Household contacts of patients with drug-resistant tuberculosis are at high risk for being infected with Mycobacterium tuberculosis and for developing tuberculosis disease. To guide regimen composition for the empirical treatment of tuberculosis infection and disease in these household contacts, we estimated drug resistance profile concordance between index patients with drug-resistant tuberculosis and their household contacts. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…For example, the simulated co-prevalence of active disease in households at the time of contact investigation (3·6% [IQR 3·4 – 4·9%]) is consistent with estimates ranging from 2·87% to 3·29% in previous systematic reviews 17-19 ; the prevalence of TB infection among MDR-TB contacts (69% [IQR 68 – 77%]) is consistent with the 72% prevalence observed a multi-country feasibility study for an ongoing TPT trial 2 ; and the simulated strain concordance of co-prevalent TB cases found during MDR-TB contact investigation (81% [IQR 70 – 98%] and among MDR-TB contacts developing incident TB in the two years following contact investigation (80% [IQR 78 – 83%]) is consistent with the 82·6% (72·3-90·9%) isoniazid and rifampin concordance estimated in a systematic review of secondary cases in the households of patients with drug-resistant TB. 20 Compared to related modeling analyses, our estimate that delamanid TPT prevents ∼51% of incident MDR-TB among all TPT recipients is consistent with a previously published estimate of ∼55% incidence reduction among pediatric contacts. 21 .…”
Section: Discussionsupporting
confidence: 89%
“…For example, the simulated co-prevalence of active disease in households at the time of contact investigation (3·6% [IQR 3·4 – 4·9%]) is consistent with estimates ranging from 2·87% to 3·29% in previous systematic reviews 17-19 ; the prevalence of TB infection among MDR-TB contacts (69% [IQR 68 – 77%]) is consistent with the 72% prevalence observed a multi-country feasibility study for an ongoing TPT trial 2 ; and the simulated strain concordance of co-prevalent TB cases found during MDR-TB contact investigation (81% [IQR 70 – 98%] and among MDR-TB contacts developing incident TB in the two years following contact investigation (80% [IQR 78 – 83%]) is consistent with the 82·6% (72·3-90·9%) isoniazid and rifampin concordance estimated in a systematic review of secondary cases in the households of patients with drug-resistant TB. 20 Compared to related modeling analyses, our estimate that delamanid TPT prevents ∼51% of incident MDR-TB among all TPT recipients is consistent with a previously published estimate of ∼55% incidence reduction among pediatric contacts. 21 .…”
Section: Discussionsupporting
confidence: 89%
“…A proportion of co-prevalent or incident tuberculosis among household contacts was assumed to be rifampicin susceptible (ie, non-concordant), unvarying by country, and 83% concordant (based on data from Chiang and colleagues). 19 The proportion of household contacts with multidrug-resistant or rifampicin-resistant tuberculosis who also had fluoroquinolone resistance in each country was based on WHO data, using a Bayesian scheme to estimate the proportion of rifampicin-resistant tuberculosis with fluoroquinolone resistance in each country 3 ( appendix pp 3–5 ). The probability that tuberculosis in child contacts was detected and was treated without HCM was based on the country-specific and age-specific WHO case detection ratio but inflated upwards by a random value between 1 and 2, truncating at 1, 11 because notified index patients' contacts might have above-average likelihood of detection.…”
Section: Methodsmentioning
confidence: 99%
“…Chiang SS și coaut. (2021) relatează concordanța profilului de rezistență între cazuri secundare și cazurile index ale acestora în 54,3% [10]. Parr JB, ș.a.…”
Section: Discuțiiunclassified